Immunomodulatory Effects and Induction of Apoptosis by Different Molecular Weight Chitosan Oligosaccharides in Head Kidney Macrophages From Blunt Snout Bream (Megalobrama amblycephala) - Wu, Changsong; Dai, Yishan; Yuan, Gailing; Su, Jianguo; Liu, Xiaoling (Frontiers in Immunology, 2019)
Prophylactic administration of immunopotentiators has been tested and practiced as one of the most promising disease prevention methods in aquaculture. Chitosan oligosaccharide (COS), as an ideal immunopotentiator, is mainly used as feed additives in aquaculture, and the antimicrobial and immune enhancement effects are highly correlated with molecular weight (MW), but little is known about the mechanisms in teleost. Here, we isolated and purified macrophages in head kidney from blunt snout bream (Megalobrama amblycephala), stimulated with three different MW (~500 Da, ~1000 Da and 2000~3000 Da) COSs, performed RNA-sequencing, global transcriptional analyses, and verified by quantitative real-time PCR (qRT-PCR) and immunofluorescent staining methods. Differential expression gene (DEG) analysis indicated that gene expression patterns are different and the proportion of unique genes are relatively high in different treatment groups. Biological process and gene set enrichment analysis (GSEA) demonstrated that all the three COSs activate resting macrophage but the degrees are different. Weighted gene co-expression network analysis (WGCNA) reflected gene modules correlated to MW, the module hub genes and top GO terms showed the activation of macrophage was positively correlated with the MW, and larger MW COS activated cell death associated GO terms. Further use of the screening and enrichment functions of STRING and Pfam databases discovered that apoptosis-related pathways and protein families were activated, such as P53 pathway and caspase protein family. qRT-PCR results showed that as the stimulation time extends, the innate immune-related and P53 pathways are gradually activated, and the degree of activation is positively correlated with the stimulation time. In addition, apoptosis was detected by immunofluorescent staining in three groups. Therefore, the use of COS has two sides, it can activate immune system against pathogen invasion, but with the increase of stimulation time and MW, macrophage apoptosis is induced, which may be caused by abnormal replication of DNA and excessive inflammation. This study provides a theoretical basis for the rational use of COS as an immunopotentiator in aquaculture.